Spontaneous regression of lumbar disc herniation after weight loss: Case report - Tokmak, Mehmet; Baltepe Altıok, İnci; Güven, Mustafa; Aras, Adem Bozkurt; Coşar, Murat (Turkish Neurosurgical Society, 2015)
Diagnosis, treatment, and surgery for lumbar disc herniations have existed for over a century. However, during the last three decades, there have been many new developments in imaging techniques, surgical procedures, physical medicine, and rehabilitation. In light of this, the most effective and appropriate treatment is controversial. Spontaneous regression of sequestrated, extruded, or protruded disc herniation has often been reported in the literature, although it is still a rare phenomenon. After a thorough review of the literature, we did not find any case report about this phenomenon after weight loss. In this report, though, we present a recent case about spontaneous regression of extruded disc herniation following weight loss.

Lomber disk hernisi için tanı, tedavi ve cerrahi yaklaşık yüz yıldır bilinmektedir. Bununla birlikte son 30 yıl içinde görüntüleme tekniklerinde, cerrahi tekniklerde ve fizik tedavi rehabilitasyonda birçok yeni gelişmeler olmuştur. Bunun ışığında, en etkili ve uygun tedavi halen tartışmalıdır. Sekestre, ekstrüde veya protrüde disk hernisinin spontan regresyonu literatürde sıkça bildirilmiş olmasına rağmen hâlâ nadir bir fenomendir. Bu fenomen hakkında literatürü taradığımızda, zayıflama sonrası disk hernisinin spontan regrese olduğuna dair bir olgu sunumuna rastlanmadı. Bu olguda zayıflamayı takiben ekstrüde disk hernisinin spontan regrese olduğu gösterildi.
Zayıflama sonrası lomber disk herniasyonunun spontan regresyonu: Olgu sunumu
Keywords: Conservative Management; Lumbar Disc; Disc Herniation; Discectomy; Konservatif Yaklaşım; Lomber Disk; Disk Herniasyonu; Diskektomi